MANAJEMEN BK DALAM PENDIDIKAN ISLAM - Samriana; Saputri, Andi Aprilia; Azizah, Wahyu Sukma Nur; Maryati, Sulis (Sindoro: Cendikia Pendidikan, 2024)
Guidance and Counseling (BK) management in Islamic Education plays a crucial role in guiding students to achieve educational goals that are in line with Islamic values. This abstract explores the strategy of implementing guidance and counseling management in Islamic education, which includes the development of Islamic guidance and counseling curriculum and programs as well as the competence of guidance and counseling teachers. In addition, it also discusses the application of counseling management functions in Islam, including the application of management functions in the process of implementing Islamic counseling and counseling management functions in general.